Terapia Ocupacional e Saúde Mental na e com a comunidade: análise de uma experiência - Roman, Loise Carlos (Universidade Federal de São Carlos, 2025)
This study aims to analyze my experience as an Occupational Therapy student in a mental health promotion group within the community, coordinated by an Occupational Therapist. Based on the principles of Popular Education and Psychosocial Care, the project “Território do Cuidar”, immersed in the social dynamics of oppressions, suffering, and possibilities, seeks to enable the production of life, meaning, and sociability through collective construction and the valorization of popular knowledge. The objective was to understand how the experience as an extensionist contributed to my education, using the experience report to describe and reflect on the practices experienced. It was observed that the approach to the community and territory revealed the potential of the collective, in which, through welcoming, belonging, sharing, lovingness and affection, it is possible to generate transformation and promote mutual and shared care that overflows into the daily lives of the participants. It is concluded that the experience in “Território do Cuidar” allowed me to be affected by the practices experienced, generating transformations, guiding my education and professional practice, and expanding my understanding through the diverse practices of Occupational Therapy. This experience reaffirms the importance of the university’s approach and joint construction with the territory, in order to promote a practice that is increasingly contextualized and transformative.
Occupational Therapy and Mental Health in and with the community: an analysis of an experience
Keywords: Terapia Ocupacional; Comunidade; Formação em Saúde; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 3. Saúde e Bem-Estar